PP10 Green and Black Tea for the Primary Prevention of Cardiovascular Disease (CVD): A Cochrane Systematic Review. (10th September 2013) - Hartley, L C; Flowers, N; Holmes, J; Clarke, A; Stranges, S; Hooper, L; Rees, K
Abstract : Background: There is increasing evidence that both green and black tea are beneficial for cardiovascular disease (CVD) prevention. Objective: Determine the effects of green and black tea on the primary prevention of CVD. Methods: The following electronic databases were searched with no language restrictions from their inception to October 2012: MEDLINE, EMBASE, CINAHL, Web of Science, the Cochrane Library and trial registers. Included studies fulfilled the following criteria: study design - RCTs, participants - free of CVD (includes those at high risk), intervention – Green tea, Black tea or tea extracts, comparator – no intervention or placebo, outcomes – diagnosis of CVD or change in the risk factor profile for CVD (blood pressure, lipids). Two reviewers independently screened titles and abstracts, assessed shortlisted studies for formal inclusion/exclusion, abstracted data and assessed methodological quality. Results: Database searching resulted in1733 hits of which 130 went forward for formal inclusion/exclusion. Nine RCTs met the inclusion criteria. Five trials examined green tea extracts and four examined black tea extracts. No studies reported cardiovascular events. Black tea extracts were found to produce statistically significant reductions in LDL cholesterol (mean difference -0.46mmol/l [95% CI -0.54, -0.39]) and blood pressure (SBP - mean difference -1.85mmHG [-32.6, -0.44]; DBP - mean difference -1.32mmHG [-2.7, -0.06]), but only a small number of trials contributed to each analysis and studies were at some risk of bias. Green tea extracts were also found to produce statistically significant reductions in total cholesterol (mean difference -0.65 mmol/l [-0.81, -0.50]), LDL cholesterol (mean difference -0.58 mmol/l [-0.87, -0.28]) and blood pressure (SBP - mean difference -3.43 mmHG [-4.54, -2.31]), but only three studies contributed to each analysis. When both tea types were analysed together they showed favourable effects on LDL cholesterol (mean difference -0.47 mmol/l [-0.54, -0.40]) and blood pressure (SBP - mean difference -2.27 mmHG [-3.44, -1.11]; DBP mean difference -2.60 mmHG [-3.46, -1.73]). Conclusion: There are very few long term studies examining the intake of green or black tea for the primary prevention of CVD. The limited evidence suggests that tea has favourable effects on CVD risk factors, but due to the small number of trials contributing to each analysis the results should be treated with caution and further high quality trials with longer term follow-up are needed to confirm this.